2021
DOI: 10.1038/s41598-021-85710-8
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and altitudinal patterns of carbon and nitrogen storage in various forest ecosystems in the central Yunnan Plateau, China

Abstract: The carbon (C) pool in forest ecosystems plays a long-term and sustained role in mitigating the impacts of global warming, and the sequestration of C is closely linked to the nitrogen (N) cycle. Accurate estimates C and N storage (SC, SN) of forest can improve our understanding of C and N cycles and help develop sustainable forest management policies in the content of climate change. In this study, the SC and SN of various forest ecosystems dominated respectively by Castanopsis carlesii and Lithocarpus mairei … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Wani et al [13] recorded a positive but weak relationship (R 2 = 0.02) between aboveground biomass carbon and elevation (m, asl). In a similar study, Li et al [19] found a strong positive relation (R 2 = 0.57) of biomass carbon with elevation. Moreover, Liu and Nan [4] also reported the direct dependency of carbon stock and altitude across three forests of Loess Plateau (China).…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Wani et al [13] recorded a positive but weak relationship (R 2 = 0.02) between aboveground biomass carbon and elevation (m, asl). In a similar study, Li et al [19] found a strong positive relation (R 2 = 0.57) of biomass carbon with elevation. Moreover, Liu and Nan [4] also reported the direct dependency of carbon stock and altitude across three forests of Loess Plateau (China).…”
Section: Discussionmentioning
confidence: 73%
“…Sun et al [72] reported a strong positive relation (R 2 = 0.67) of ABG biomass with elevation in the central highland, Vietnam. Furthermore, the findings of Li et al [19] exposes no significant interaction of altitude with vegetation carbon stock in Chitteri reserve forest.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Li et al, 2021 also found that nitrogen storage in various forest ecosystems in the central Yunnan Plateau ranged from 4.47 ± 0.94 t ha −1 in Pinus yunnanensis to 8.91 ± 1.83 t ha −1 in Pinus armandii [20]. Soil, plants and litter contributed an average of 86.88%, 10.27% and 2.85% to forest nitrogen storage, respectively [20].…”
Section: Introductionmentioning
confidence: 99%